ミズホ コウゲン ノ キバン ヒョウメン チケイ オヨビ セキセツ ノ タイセキ ニ ツイテ - 西尾, 文彦; ニシオ, フミヒコ; 楠, 宏; クスノキ, コウ; NISHIO, Fumihiko; KUSUNOKI, Kou (国立極地研究所, 1975)
P(論文) Results are presented of spectral analyses of the net snow accumulation, surface and bedrock profiles along the meridian of about 40°E, from Syowa Station to the South Pole, traversed by the Japanese party in 1968-1969. There is a clear trend of increase of the wavelength of the surface maximum amplitude going inland. The prevailing wavelength of the surface undulation increases clearly toward the inland. The "damping factor" or ratio of the bedrock amplitude to the surface amplitude has a minimum when the wavelength of the surface undulation is about 3 or 4 times of the mean ice thickness. The accumulation pattern in the katabatic wind region is strongly influenced by the surface topography on both large and small scales; the maximum accumulation occurs near the ridge and the wind-ward side of slope while the minimum in the trough and lee-wind side. departmental bulletin paper